Evaluasi Proses Bisnis Pendaftaran Nikah Menggunakan Metode Business Process Improvement (BPI) di KUA - Amanda Julia Dela Siska; Pacu Putra; Dinna Yunika Hardiyanti; Muhammad Ihsan Jambak (STMIK Budi Darma, 2023)
The Indralaya District Religious Affairs Office is a government agency authorized to carry out some of the duties of the Ministry of Religious Affairs. Registration and recording of marriages is one of the duties of the Sub-district KUA. However, in carrying out its duties, there are several obstacles faced in the current flow of marriage registration, such as the length of the marriage registration process, and a complicated process due to the many documents that must be taken care of to various agencies. Therefore, it is necessary to conduct periodic evaluations to find potential problems that hinder the current business process and optimize the quality of services of the sub-district KUA. The current marriage registration flow and the recommended marriage registration flow will be modeled using a Business Process Model and Notation (BPMN) diagram. Then, each activity in the current marriage registration flow is evaluated using the Failure Mode and Effects Analysis (FMEA) approach. The results of the FMEA evaluation are used for business process improvement. Business process improvement is carried out using the Business Process Improvement (BPI) method. BPI is a method used to improve the quality of business processes to make them more effective and efficient without having to reconstruct ongoing business processes radically. After that, the design of business process recommendations will be proposed using tools from the third phase of BPI, namely streamlining. Furthermore, simulations will be carried out using Bizagi Modeler to test time, process validation, and resource analysis. The results obtained are an increase in process time from 28 days 2 hours 56 minutes 30 seconds to 10 days 9 hours 27 minutes 15 seconds or an increase of 62.80%.